Sebuah PERANCANGAN SISTEM INFORMASI PEMBUATAN AKTA KELAHIRAN BERBASIS WEB DENGAN MENGGUNAKAN METODE WATERFALL DI KECAMATAN CISEENG KABUPATEN BOGOR: PERANCANGAN SISTEM INFORMASI PEMBUATAN AKTA KELAHIRAN BERBASIS WEB DENGAN MENGGUNAKAN METODE WATERFALL DI KECAMATAN CISEENG KABUPATEN BOGOR - Mutadin; Yulianti (Journal of Research and Publication Innovation, 2023)
Currently, information technology plays an important role in human activities that can be utilized by the community and government sectors, with one of them being in government management at the sub-district and city levels. The Ciseeng sub-district office, Bogor district, is one of several sub-district government institutions that utilize information technology to inform and improve existing services. The Ciseeng District, Bogo Regency, does not yet have a complete service information system for the community in making a child's birth certificate. So this study aims to design an information system for making child birth certificates in Ciseeng District, Bogor Regency. The methodology used in this information system research is the waterfall methodology, the results of this research will facilitate the community in making a child's birth certificate. The preparation of this information system is intended as a means of increasing awareness of making birth certificates for children and providing good solutions for the community and sub-districts. So, with the existence of an information system for making child birth certificates, it can improve and facilitate the community in making birth certificates and assisting the government in managing information data.